Anterior tibial spine (ACL avulsion) fracture treated with open reduction and fixation with screw: surgical technique, functional and clinico-radiological outcomes - V. Chawda, Rajesh; J. Patel, Vijay; M. Ninama, Dhaval; N. Patel, Harsh (International Journal of Research in Orthopaedics, 2019)
Background: The anterior tibial spine fracture occurs almost at a same frequency both in adolescents and in adults. These injuries are often overlooked at emergency room. Stable internal fixation requires to gain optimum function of ACL by securing its length and nascent tension. We treated anterior tibial spine (ACL avulsion) fracture patient with open reduction and screw fixation. Methods: Study of Ten patients of anterior tibial spine (ACL avulsion) fracture, with minimum of 06 months and maximum of 18 months follow up. Classification of anterior tibial spine (ACL avulsion) a fracture done by Meyer and Mckeever. All patients operated with open reduction and internal fixation with screw via medial parapatellar approach. Functional and clinical outcome measured with Lysholm knee score at final follow up. Results: We studied 10 patients with anterior tibial spine (ACL avulsion) fractrure where mean age of patient was 36.4 years. Mean radiological healing was 10.6 weeks in anterior tibial spine (ACL avulsion) fracture. We observed mean motion of knee 133 degree in anterior tibial spine (ACL avulsion) fracture. Mean Lysholm score at final follow up was 86.8. Conclusions: Open reduction for anterior tibial spine (ACL) fracture provides direct visualization with easy application of screws ultimately confers stable osteosynthesis enables to start early range of motion and further rehabilitation protocol. Open reduction internal fixation is comparative less technically demanding, less expansive and gives excellent to good results as compared to other techniques.